1995
DOI: 10.1111/j.1945-5100.1995.tb01169.x
|View full text |Cite
|
Sign up to set email alerts
|

Cristobalite‐ and tridymite‐bearing clasts in Parnallee (LL3) and Farmington (L5)

Abstract: A set of cristobalite-and tridymite-rich igneous clasts (CB1 to CB8) have been found in Parnallee (LL3.6). They consist of clinoenstatite, minor feldspathic mesostasis and cristobalite veined by endiopsideaugite. The largest clast, CB8, is 1.6 cm in diameter and contains veined tridymite and cristobalite, clinoenstatite (zoned to ferroaugite and pyroxferroite Fs75.6Wo20.0) and plagioclase. Compared to bulk ordinary chondrites (OC), the bulk clasts are depleted in A1 (0.02-0.8~ OC), Na and K and enriched in Si … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
42
0

Year Published

2000
2000
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 40 publications
(44 citation statements)
references
References 40 publications
(39 reference statements)
2
42
0
Order By: Relevance
“…We believe the most straightforward explanation is that this occurred through crystal-melt fractionation in a planetary setting, although Brigham et al proposed a nebular setting for olivine-gas fractionation. In addition to the bulk major element compositions, the evidence for a planetary origin (in clasts with similar mineral assemblages to the Bo Xian chondrules) is the presence of bulk low rare earth element abundances greater than high rare earth element abundances with a positive Eu anomaly in one sample (Bridges et al, 1995). Such trace element abundances are compatible with crystal-melt fractionation but not volatilisation.…”
Section: Chondrule Textures and Chemical Fractionationmentioning
confidence: 93%
See 3 more Smart Citations
“…We believe the most straightforward explanation is that this occurred through crystal-melt fractionation in a planetary setting, although Brigham et al proposed a nebular setting for olivine-gas fractionation. In addition to the bulk major element compositions, the evidence for a planetary origin (in clasts with similar mineral assemblages to the Bo Xian chondrules) is the presence of bulk low rare earth element abundances greater than high rare earth element abundances with a positive Eu anomaly in one sample (Bridges et al, 1995). Such trace element abundances are compatible with crystal-melt fractionation but not volatilisation.…”
Section: Chondrule Textures and Chemical Fractionationmentioning
confidence: 93%
“…The other two chondrules (BX71, BX122) have 2 and 10 vol% cristobalite, respectively. Previous x-ray diffraction (XRD) analyses of pyroxene-silica clasts in ordinary chondrites have shown that cristobalite is the most likely identity of the silica polymorph (Bridges et al, 1995).…”
Section: Chemically Fractionated Chondrulesmentioning
confidence: 99%
See 2 more Smart Citations
“…Moreover, sputtering ofsolids by energetic particles ejected by the YSO might have contributed a small proportion of refractory elements to the condensates. Cristobalite-and tridymite-bearing clasts that have been observed in a few ordinary chondrites (Bridges et al, 1995) are a compositional match for this hypothetical component. The clasts are < 16mm in size and composed of a silica polymorph + enstatite ± Capyroxene ± Ca-plagioclase.…”
Section: Origin Of the Silicon-and Magnesium-rich Component-fractionamentioning
confidence: 82%